Dampak DER Dan ROE Terhadap Peringkat Obligasi Sektor Perbankan - AlQusyairi, Nurhadi; Juwita, Ratna (Universitas Multi Data Palembang, 2024)
This study aims to see the effect of Debt to Equity Ratio (DER) and Return On Equity (ROE) on the rating of banking sector bonds listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The data used is 619 banking sectors, using purposive sampling method so that 43 bonds are obtained. The results of the research conducted show that Debt to Equity Ratio has a significant effect on Bond Rating. While Return On Equity has no significant effect on Bond Rating.